Link connectivity under more realistic channel model for vehicle-to-vehicle communications. (2016) - Chen, Ruifeng; Zhong, Zhangdui; Leung, Victor C.M.; Michelson, David G.
Since the antennas are very low in vehicle-to-vehicle (V2V) scenarios, the communication link is easily blocked by other vehicles. The shadowing effect caused by other vehicles has been ignored in most of the existing V2V channel models, and it is thus neglected in the system performance evaluation. By incorporating channel state transition with a measurement-based dual-slope path loss model, an obstacle-based model is presented in this paper for the V2V highway scenarios to capture the dynamic characteristics of radio channels, in the presence of other vehicles as moving obstacles. The joint effects of the radio environment and traffic flow on link connectivity are mainly investigated. The obstruction probability is represented, and the connectivity-related metrics are evaluated: inter-vehicle connectivity probability and link duration. All the analytical results are validated by extensive simulations under the measurement-based path loss model, and are also compared to the existing models.